Socio Economic Conditions Of Construction Workers In Tamilnadu: Issues And Challenges - Seenivasan, R. (Journal of Islamic Economics and Social Science (JIESS), 2023)
The present study is aimed to explore socio-economic problems of Tamilnadu women workers at construction sites in working environment and to document issues like gender bias, living conditions, vulnerability and slackness, wages, their economic status by finding out their savings, loan etc. The author concentrated only on the women workers who are working in the construction sector and how they are facing problems in the work place. Majority of the women construction workers are facing lots of problems like absence of social security, low wages, gender discrimination, unhygienic conditions at work place etc. Data was collected from 160 women workers from four areas of Tamilnadu (North, East, West, South) city. The data for this study has been collected through primary source. The primary for this study was collected with the help of the questionnaire. The secondary data was collected from the library and websites. The major findings of construction women labor facing many problems they asked government security for their jobs.